Opioid withdrawal presenting as delirium and role of buprenorphine: A case series - Sourav Das; Divyashree Sah; Shiladitya Nandi; Payel Das (Indian Journal of Psychological Medicine, 2017)
Opioid withdrawal is very rarely characterized by delirium unlike alcohol or benzodiazepine withdrawal. PubMed search through October 2016 reveals only two case series on delirium as feature of withdrawal in opioid dependence syndrome. We report two cases of opioid withdrawal (heroin) presenting with delirium when low-dose buprenorphine (2 mg/day) was added. Both the cases had no other substance abuse history and nil contributory past and family history. Both of them were improved after increasing the buprenorphine dosage to 6–8 mg/day. The possibility of delirium as a part of withdrawal symptom or as a phenomenon induced by buprenorphine or due to impurities in the heroin used is discussed.